A simplified analytical model for metal sandwich beam with soft core under impulsive loading over a central patch - Qin, Qinghua; Yuan, Chao; Zhang, Jianxun; Wang, T.J. (International journal of impact engineering, 2014)
A simplified analytical model is proposed to predict the large deflection response of fully clamped metal sandwich beam with soft core subjected to impulsive loading over a central patch. Using the classical yield condition for sandwich cross-section, the dynamic response is uncoupled into two distinct phases: a bending-only phase and a plastic string phase. Analytical solutions for the metal sandwich beams under impulsive loading are then obtained. Comparisons of the analytical predictions with finite element results manifest that the simplified analytical model can accurately capture the dynamic response of sandwich structure with a soft core. Finally, the analytical formulae are employed for the minimum mass design of sandwich structures. •A simplified model for impulsive loading of metal soft core sandwich beam is developed.•The yield criterion of a rectangular sandwich cross-section is approximated by a straight line.•The dynamic response is uncoupled and separated into two distinct phases.